1991
DOI: 10.1099/00221287-137-3-549
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall and autolytic system of Lactobacillus helveticus ATCC 12046

Abstract: The cell wall of Lactobacillus helveticus was found to have a three-layered structure when thin sections of whole cells or isolated cell walls were stained by various procedures and examined by electron microscopy. The main feature of the composition of isolated cell walls was a high protein content (about 48% of the cell wall dry weight) with a predominant 52 kDa protein. Peptidoglycan and what was considered as teichoic acids accounted for 36% and 14%, respectively, of the cell wall dry weight. The 52 kDa pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…However, concurring with previous publications, the thermophilic bacteria generally disappeared in a brief time (1-3 months), thus releasing a wealth of enzymes [3,7,8,17,31]. An undoubtedly important contribution was made by the mesophilic lactic acid bacteria (essentially L. casei, L. paracasei, L. rhamnosus, pediococci) which presented meaningful counts in the fifth month of ageing, thereby showing a significantly higher level compared to what has been reported thus far in literature with specific reference to Grana Padano [1].…”
Section: Discussionmentioning
confidence: 53%
“…However, concurring with previous publications, the thermophilic bacteria generally disappeared in a brief time (1-3 months), thus releasing a wealth of enzymes [3,7,8,17,31]. An undoubtedly important contribution was made by the mesophilic lactic acid bacteria (essentially L. casei, L. paracasei, L. rhamnosus, pediococci) which presented meaningful counts in the fifth month of ageing, thereby showing a significantly higher level compared to what has been reported thus far in literature with specific reference to Grana Padano [1].…”
Section: Discussionmentioning
confidence: 53%
“…Quantitative amino acid and hexosamine analyses were performed as described by Lortal et al (1991). The phosphorus content was determined according to Eckman (1993) using sodium dihydrogen phosphate as standard.…”
Section: Methodsmentioning
confidence: 99%
“…LiCl treatment eliminates the outer layer observed by electron microscopy, so the surface exposed after this treatment is considered to be the intermediate layer (Lortal et al, 1991). Given the high surface oxygen and low surface nitrogen of treated cells (Table 2), the high proportion of the carbon peak component at 286.3 eV (Table 3) )I Hydrocarbon-like compound (CH,).…”
Section: Treated Cellsmentioning
confidence: 99%
“…Previous work (Lortal et al, 1991) showed that the outermost layer of the cell wall was composed of a nonglycosylated 52 kDa protein. In this investigation, several procedures for extracting the S-layer protein from whole cells and isolated cell walls were tested (Table 1).…”
Section: Isolation Purification and Chemical Characterization Of Thementioning
confidence: 99%
“…In previous work (Lortal et at., 1991) the cell wall of L. helveticus ATCC 12046 was found to have a three-layered structure. The external layer was shown to be composed of a 52 kDa protein, non-covalently linked to the internal layers.…”
Section: Introductionmentioning
confidence: 99%